Clinical courses of herpes simplex virus-induced urethritis in men. Issue 10 (October 2017) - Ito, Shin; Yasuda, Mitsuru; Kondo, Hiromi; Yamada, Yoshiteru; Nakane, Keita; Mizutani, Kosuke; Tsuchiya, Tomohiro; Yokoi, Shigeaki; Nakano, Masahiro; Deguchi, Takashi
Abstract: We retrieved clinical data of 13 men having herpes simplex virus (HSV)-induced non-gonococcal urethritis (NGU) without visible herpetic lesions. They visited a clinic in Sendai, Japan, between April 2013 and December 2015. All the men complained of dysuria. Meatitis was observed in 9 of the 13 men. Mononuclear cells were observed in the urethral smears from 9 men. The 13 men were treated with azithromycin or sitafloxacin regimen. First-voided urine (FVU) specimens became negative for HSV in 8 of the 10 men who returned to the clinic after antibacterial treatment, and urethritis symptoms were alleviated. However, herpetic lesions were observed at the follow-up visits in 3 men, and 2 of them were still positive for HSV in their FVU. HSV could be a cause of acute urethritis without causing visible herpetic lesions. The shedding of HSV from the urethra would spontaneously cease with alleviation of urethritis symptoms in most cases of HSV-induced NGU without antiviral therapy. However, new herpetic lesions could be developed in some cases. Early antiviral therapy is beneficial for patients with HSV infections. The development of meatitis and the mononuclear cell response in the urethral smear could be helpful to diagnose HSV-induced NGU. Therefore, we should presumptively initiate anti-HSV therapy for patients with signs and symptoms suggestive of HSV-induced NGU at their first presentation.